2021
DOI: 10.3390/molecules26123513
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Lam. in Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: Plant-derived phytochemicals have been interested in as nutraceuticals for preventing the onset and progress of diabetes mellitus and its serious complications in recent years. Moringa oleifera Lam. is used in vegetables and in herbal medicine for its health-promoting properties against various diseases including diabetes mellitus. This study aimed to examine an effect of Moringa oleifera on diabetic hyperglycemia and dyslipidemia by meta-analyzing the current evidence of diabetic rodent models. Peer-reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…These results are consistent with some preclinical findings ( Jaja-Chimedza et al, 2018 ; Mohamed et al, 2019 ), indicating that Moringa oleifera leaf extracts might be useful complications identified during the early development of T2D. Nonetheless, despite accumulative literature, as reviewed elsewhere ( Ba et al, 2020 ; Watanabe et al, 2021 ), indicating that this plant might present with important antidiabetic properties, more needs to be done to confirm these in clinical settings. It remains crucial, to evaluate whether Moringa oleifera leaf extracts can prominent biomarkers of oxidative stress and inflammation, to verify preclinical findings.…”
Section: Clinical Translationsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with some preclinical findings ( Jaja-Chimedza et al, 2018 ; Mohamed et al, 2019 ), indicating that Moringa oleifera leaf extracts might be useful complications identified during the early development of T2D. Nonetheless, despite accumulative literature, as reviewed elsewhere ( Ba et al, 2020 ; Watanabe et al, 2021 ), indicating that this plant might present with important antidiabetic properties, more needs to be done to confirm these in clinical settings. It remains crucial, to evaluate whether Moringa oleifera leaf extracts can prominent biomarkers of oxidative stress and inflammation, to verify preclinical findings.…”
Section: Clinical Translationsupporting
confidence: 87%
“…Dixit and co-workers (Dixit et al, 2018) Mohamed et al, 2019), indicating that Moringa oleifera leaf extracts might be useful complications identified during the early development of T2D. Nonetheless, despite accumulative literature, as reviewed elsewhere (Ba et al, 2020;Watanabe et al, 2021), indicating that this plant might present with important antidiabetic properties, more needs to be done to confirm these in…”
Section: Clinical Translationmentioning
confidence: 97%
“…Numerous reports have confirmed the role of citrus peels' antidiabetic and antihyperlipidemic properties (Muhtadi et al, 2015), and Ademosun et al (2021) reported the ability of orange peels in unripe plantain noodles in reducing glycemic index in rats. The role of moringa ( Moringa oleifera ) leaves cannot be overemphasized in the management of hypertension, hyperlipidemia (Oyeleye et al, 2019), and chronic hyperglycemia (Watanabe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of the evidence is provided by in vitro experiments and studies in animal models (91). Besides, a recent meta-analysis of 46 studies in animal models suggested a potential role of Moringa-derived products in the reduction of glucose and lipid levels (92).…”
Section: Africamentioning
confidence: 99%